Ethnogeographic Features of Tuberculosis Incidence in the South Aral Sea Region - D. A. Asadov; A. K. Khamraev; G. K. Yuldashev (Туберкулез и болезни лёгких)
The objective: to conduct comparative analysis of tuberculosis incidence of among ethnic groups living in the South Aral Sea region and to establish whether belonging to the Karakalpak ethnic group presents a risk factor of developing tuberculosis.Subjects and Methods. Tuberculosis incidence over 5 years (2016-2020) among people of Uzbek and Karakalpak ethnicities living in the Republic of Karakalpakstan was compared and retrospectively analyzed.Results. In 2016-2020, tuberculosis incidence among people of the Karakalpak ethnicity (whose ancestors were nomadic and seminomadic people) made 147,08 per 100,000 population on the average (2016 - 178,8; 2017 - 174,8; 2018 - 139,4; 2019 - 136,9; 2020 - 108,1 per 100,000 population), among people of the Uzbek ethnicity (whose ancestors lived sedentary lives), tuberculosis incidence made 85,3 per 100,000 population on the average (2016 - 92,4; 2017 - 89,5; 2018 - 139,4; 2019 - 136,9; 2020 - 60,9 per 100,000 population). A statistically significant difference was demonstrated in tuberculosis incidence among people of the Karakalpak and Uzbek ethnic groups.